Pediatric oncology services in Colombia - Suarez Mattos, Amaranto; Aguilera, Jairo; Salguero, Edgar Augusto; Wiesner, Carolina (Colombia Medica, 2018)
Background: In low-income countries, a child diagnosed with cancer has an 80% chance of dying, while in high-income countries more than 80% survive the disease. In Colombia, a middle-income country, the government issued new legislation that promotes the generation of comprehensive care units; nevertheless, seven years after its expedition, no institution has been recognized as such by the Ministry of Health. Objective: To characterize the current offer of oncological services for cancer care in children and to identify the institutions that could be constituted in Units of Comprehensive Care of Childhood Cancer in Colombia.Methods: descriptive study of secondary source, it was consulted the Special Register of Health Providers of the Ministry of Health and Social Protection, in order to identify the institutions that had enabled hospitalization services of medium or high complexity, chemotherapy, specialized consultation, emergencies, oncological surgery, radiotherapy or nuclear medicine. The information is reported in absolute frequencies. Results: Seventy one institutions have hematology-oncology consultation, 39 institutions have chemotherapy and hospitalization services of medium or high complexity, and 18 have radiotherapy enabled. Only nine of the institutions include all the services that are necessary for comprehensive care. Conclusion: Colombia has a sufficient supply of services for the care of children with cancer. Only a minority are in institutions that have the capacity to guarantee the integrality of the attention.